DETERMINING COUNTRIES' POTENTIALS FOR SUCCESSFUL EXPORT OF LUXURIOUS AND BANKING SERVICES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Country's economic potential implies joint capability of the country's economy, its branches and enterprises to carry out production and economic activity, to create goods and services, to supply the demand of the population, to stimulate production and consumption development. Country's economic potential is defined by estimating different economic, social, ecological, scientific and technical, political and other criteria, which, as a rule, are interconnected and correlated. Each of these criteria includes heterogeneous set of economic, financial, social, political, juridical, educational, scientific and innovational, ecological, cultural and other factors, every single of which can consist of independent or indirectly correlated subfactors called indices or indicators. In this work we investigate the problem of estimating economic potentials of groups of countries according to their measurable economic, financial, social and other indicators in order to export bank and other luxurious services. The approach to solving the problem offered in this work is based on the apparat of the theory of inverse and ill-posed problems.